Analysis of Kinayah in the Qur'an Bayan Science - Rohman, Abd; Nuruddien, Muhammad (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the phenomenon of kināyah usage in the Qur'an as one of the stylistic expressions (uslūb) within the science of balāghah, particularly in the branch of bayān. As a rhetorical device, kināyah possesses distinct characteristics because it conveys implicit (connotative) meaning while still allowing for literal (denotative) interpretation in specific contexts. This research adopts a qualitative approach by conducting a literature review of various classical and contemporary tafsir works, along with key sources in balāghah. The findings indicate that kināyah in the Qur'an is not merely a tool for beautifying language, but also serves pragmatic purposes, such as masking meanings, avoiding harshness, demonstrating respect, and conveying legal implications that impact Islamic religious practice. Several verses containing kināyah are identified in this study, including the expression “lamastum an-nisā’”, which alludes to marital intimacy. Interpretation of such kināyah verses often becomes a point of contention among exegetes due to differing understandings of qarīnah (contextual clues) and linguistic frameworks. Some interpreters take the expression literally, while others view it as a metaphor for intimate relations, highlighting the significant role of kināyah in shaping Islamic law and theology. Moreover, kināyah serves as a form of honorific language, as evidenced by the Qur'an's use of subtle expressions to replace explicit terms deemed inappropriate for direct mention. Other functions include abbreviation, embellishment, and enhancing the rhetorical impact of Qur'anic discourse. Hence, mastering balāghah, particularly bayān, is essential to properly comprehend kināyah in the Qur'anic context. By gaining a comprehensive understanding of kināyah, readers of the Qur'an will be better equipped to grasp the divine messages embedded within its eloquent language. This study is expected to contribute to the advancement of Qur'anic exegesis and the teaching of balāghah, while also enriching interpretive insights for understanding implicit and contextual meanings in the Qur'an. Thus, the research is relevant not only to Arabic linguistics but also to broader Islamic studies, particularly in enhancing contextual tafsir literacy that is responsive to social dynamics.